2021
DOI: 10.3390/jof7090771
|View full text |Cite
|
Sign up to set email alerts
|

Neopestalotiopsis Species Associated with Flower Diseases of Macadamia integrifolia in Australia

Abstract: Macadamia (Macadamia integrifolia) is native to eastern Australia and produces an edible nut that is extensively cultivated in commercial orchards in several countries. Little is known about the diversity of fungi associated with diseases of macadamia inflorescences. A survey of fungi associated with the dry flower disease of macadamia detected several isolates of Neopestalotiopsis (Pestalotiopsidaceae, Sordariomycetes). Five new species of Neopestalotiopsis were identified based on molecular phylogenetic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 51 publications
(74 reference statements)
1
18
0
Order By: Relevance
“…Neopestalotiopsis photiniae is morphologically distinguishable from N . vheenae in shorter conidiogenous cells (1 to 3 × 2 to 4 μm versus 5 to 10 × 3 to 5 μm) ( 23 ). The result of the PHI test showed that there is no obvious recombination (Фw = 1.0) between N. photiniae and its closely related taxa ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neopestalotiopsis photiniae is morphologically distinguishable from N . vheenae in shorter conidiogenous cells (1 to 3 × 2 to 4 μm versus 5 to 10 × 3 to 5 μm) ( 23 ). The result of the PHI test showed that there is no obvious recombination (Фw = 1.0) between N. photiniae and its closely related taxa ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As important plant pathogens, pestalotioid species are almost ubiquitous in agricultural and noncultivated ecosystems, causing multiple diseases and huge economic losses ( 22 30 ). For example, gray blight disease of tea plants is caused by Pseudopestalotiopsis spp.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of our amplified nucleotide sequences was checked and combined by SeqMan v.7.1.0 and reference sequences (Table 1) were retrieved from the National Center for Biotechnology Information (NCBI), according to recent publications of the genus [19][20][21]. Sequences were aligned using MAFFT v. 6 [24] and manually corrected using Bioedit 7.0.9.0 [25].…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…Pseudopestalotiopsis differs from Pestalotiopsis by having three darker median cells and knobbed apical appendages [8]. Many novel species were introduced into this group during recent years through a polyphasic approaches together with morphology [11][12][13][14][15][16][17][18][19][20][21]. This study aimed to identify the pestalotioid fungi associated with Camellia oleifera in China based on both morphological characters and molecular phylogeny.…”
Section: Introductionmentioning
confidence: 99%
“…The planted area of macadamia in China exceeded 301,206 hm 2 by the end of 2018, and now China has the largest and fastest growing macadamia industry, accounting for over 1/3 of global production acreage ( Shuai et al, 2022 ). Macadamia plants have been reported to be susceptible to a variety of fungal pathogens that can variously infect flower, leaf, fruit, stem, and root tissues ( Akinsanmi and Drenth, 2006 , 2017 ; Akinsanmi et al, 2016a , b ; Prasannath et al, 2021a , b ; Li et al, 2022 ). In this regard, species in the genus Lasiodiplodia represent a serious concern for the crop.…”
Section: Introductionmentioning
confidence: 99%